2020
DOI: 10.36227/techrxiv.12130809.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Latency-Aware Offloading in Integrated Satellite Terrestrial Networks

Abstract: Next-generation communication networks are expected to integrate newly-used technologies in a smart way to ensure continuous connectivity in rural areas and to alleviate the traffic load in dense regions. The prospective access network in 6G should hinge on satellite systems to take advantage of their wide coverage and high capacity. However, adopting satellites in 6G could be hindered because of the additional latency introduced, which is not tolerable by all traffic types. Therefore, we propose a traffic off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…The results of this work showed that improved energy efficiency is achieved with a similar traffic offloading performance used in traditional terrestrial systems. Similarly, [12] has developed a traffic offloading scheme that exploits the HSTN system's capabilities to overcome the capacity limitations of the terrestrial backhaul by allocating the traffic between the satellite and the terrestrial segment while satisfying different traffic requirements. Furthermore, the authors in [13] have presented an RAN for integrated satelliteterrestrial networks, proposing a load balancing algorithm, supporting a large number of users, and increasing the network throughput.…”
Section: A Backgroundmentioning
confidence: 99%
“…The results of this work showed that improved energy efficiency is achieved with a similar traffic offloading performance used in traditional terrestrial systems. Similarly, [12] has developed a traffic offloading scheme that exploits the HSTN system's capabilities to overcome the capacity limitations of the terrestrial backhaul by allocating the traffic between the satellite and the terrestrial segment while satisfying different traffic requirements. Furthermore, the authors in [13] have presented an RAN for integrated satelliteterrestrial networks, proposing a load balancing algorithm, supporting a large number of users, and increasing the network throughput.…”
Section: A Backgroundmentioning
confidence: 99%
“…Flow sizes are independently and identically distributed with mean 1 µe for eMBB slice and 1 µu for URLLC slice, such that 1 µe and 1 µu represent the flow size for both traffic types, respectively. The total load of URLLC traffic and eMBB traffic in the v-th micro base station are denoted by L e v rts and L u v rts respectively and are assessed as [19], [20], [23]:…”
Section: A Traffic Modelmentioning
confidence: 99%
“…The achievable data rate R sat v rts between the vth micro base station and the satellite at time slot t is expressed as [13], [23]:…”
Section: Satellite Down-link Data Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of wireless backhauling over traditional wired backhauling are the implementation flexibility, cost efficiency, and lowcomplexity maintenance processes. Moreover, integrated access and backhauling is considered as a promising approach to reduce the deployment cost in ultra-dense networks [7]- [9]. Therefore, wireless backhauling has attracted extensive research attention to develop efficient backhauling solutions.…”
Section: Introductionmentioning
confidence: 99%